KONEKSI POLITIK DAN PENGHINDARAN PAJAK: SOLUSI ATAU ANCAMAN BAGI NILAI PERUSAHAAN - Rina Nurjanah; Adibah Yahya; Taufik Hidayat; Meli Andriyani (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study examines the interplay between political connections, financial distress, Tax Avoidance, and a company's firm value. The primary objective is to analyze how these factors influence firm value, particularly focusing on the effects of political connections on financial distress and Tax Avoidance. The research was conducted on 33 companies listed on the Jakarta Islamic Index (JII70) from 2022 to 2024, utilizing e-Views as the analytical tool. The findings reveal that political connections do not significantly impact firm value or Tax Avoidance; however, they do have a negative effect on financial distress. Conversely, financial distress negatively affects both firm value and Tax Avoidance, while Tax Avoidance does not influence firm value. These results suggest that a company's fundamental factors and internal conditions play a more critical role in determining its value than political connections. Consequently, the study highlights the importance for companies to prioritize robust financial performance and effective business strategies over reliance on transient political connections. Keywords: Financial Distress; Firm Value; Political Connection; Tax Avoidance.